1998
DOI: 10.2136/sssaj1998.03615995006200040017x
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Copper Rhizotoxicity by Calcium and Magnesium at Defined Free Metal‐Ion Activities

Abstract: The common “hardness cations”, Ca and Mg, are at least partially capable of alleviating the toxicities of metal ions, but quantitative data for their effect on Cu rhizotoxicity are lacking. We used 2‐d root elongation of wheat (Triticum aestivum L., cv. Yecora Rojo) in a simple medium (≥0.2 mM CaCl2) as a sensitive bioassay for examining how Ca, Mg, and pH affect Cu rhizotoxicity. A fourfold increase in solution CaT from 1 to 4 mM showed a slight alleviation of toxicity, but the effect could be completely ascr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 0 publications
4
49
0
Order By: Relevance
“…This is perhaps not too surprising, as the exchangeable Ca concentrations in the serpentine soils used in Anderson et al (1973) were low (less than 30% of total CEC), relative to what is common for nonserpentine soils (60Á80% of total CEC), thus potentially posing less competition for Ni uptake by plants ( Kinraide 1998;Parker et al 1998). The data of Weng et al (2003) suggest that the EC 25 for shoot biomass occurred at approximately 4 mmol Ni kg…”
Section: Discussionmentioning
confidence: 98%
“…This is perhaps not too surprising, as the exchangeable Ca concentrations in the serpentine soils used in Anderson et al (1973) were low (less than 30% of total CEC), relative to what is common for nonserpentine soils (60Á80% of total CEC), thus potentially posing less competition for Ni uptake by plants ( Kinraide 1998;Parker et al 1998). The data of Weng et al (2003) suggest that the EC 25 for shoot biomass occurred at approximately 4 mmol Ni kg…”
Section: Discussionmentioning
confidence: 98%
“…This is consistent with the studies for Ni toxicity by Lock et al (2007b) and also for some other metals (de Schamphelaere and Janssen 2002; Heijerick et al 2002b;Lock et al 2007a). However, more previous studies have observed a significant correlation between EC50 and pH at EC50 (Erickson et al 1996;Heijerick et al 2002a;Parker et al 1998;Thakali et al 2006a, b;Voigt et al 2006). Hence, incorporation of proton competition into the concept of BLM remains to be justified (Wang et al 2009).…”
Section: Variation and Prediction Of Ni Ec50mentioning
confidence: 96%
“…The ability of Cu to mediate high rates of electron transfer is also a potential cause of toxicity for plant cells (especially in growing roots). Less than 5 mM Cu inhibits the growth of roots in wheat (Triticum aestivum; Taylor et al, 1991;Parker et al, 1998) and Arabidopsis (Arabidopsis thaliana; Toda et al, 1999). This sensitivity of growing roots is a potential risk in agriculture that arises from the use of Cu-containing fungicides and fertilizers.…”
mentioning
confidence: 99%